Supply chain of the automobile industry: Internal control issues, operations, and sustainability of cars exported overseas - Mat Dangi, Mohamad Ridhuan; Abdul Latiff, Nurul Ezhawati; Ahmad, Emmarelda Maswesi; Asat, Siti Haliza; Mohd. Noor, Rohana (Penerbit Akademia Baru, 2017)
This paper explores the internal control issues, operations and sustainability in the supply chain of automobile industry when exporting their cars overseas. Particularly this paper emphasized the possible reasons of internal control issues and implications that cause the increase in insurance claims on Damage in Transit (DIT) and/or Missing and Discrepancy (MAD) on car exporters. Goods and items exported overseas face the risks of DIT and/or MAD that are affected by any number of causes and exposures such as natural disaster, deficiencies, criminal activity and so forth. The increase in DIT and/or MAD insurance claims has a direct impact on the company’s operating costs that requires a higher premium to be paid to the insurance company, hence reduce the revenue. The internal control weaknesses in handling the exported goods also can become one of the major reasons to DIT and/or MAD that related to criminal activities. This paper reviewed the past literatures relating to damages, missing or discrepancy happened during the process of exporting cars and the concept of internal control and some examples of the cases of companies that put it into practice. This study is expected to provide notion to the automotive industry that exporting cars overseas to evaluate their existing procedures in place and make improvisation to deliver better quality services and products to their customers and to improve the current working process in related departments if such weaknesses induced to DIT and/or MAD exists. In addition, this study also aims to improve communication between divisions to ensure and to prevent the occurrence of the same issues in the future. Finally, this study proposed the execution of COSO internal control framework and a better cost management exercise may be practiced to alleviate DIT and/or MAD.